Percutaneous kyphoplasty for osteoporotic vertebral compression fractures performed in one-day surgery: safe and effective? - An, Zhongcheng; Dou, Jiayi; Mao, Wangnan; Wu, Bing; Zhang, Han; Feng, Junwei; Chen, Chen; Tang, Binbin; Dong, Liqiang; Wu, Lianguo; Zhang, Xiaoping (Frontiers in Surgery, 2025)
ObjectiveEvaluating the safety and efficacy of percutaneous kyphoplasty (PKP) as an ambulatory surgery procedure, and analyzing causes of postoperative delayed discharge in day surgery settings.MethodsA retrospective analysis was conducted on 299 patients diagnosed with osteoporotic vertebral compression fractures (OVCFs) who required PKP surgery in our hospital's orthopedic department between January 2022 and December 2023. Among them, 157 underwent the day surgery procedure group (DSP), while 142 received the traditional inpatient group (TIP). The following parameters were recorded for both groups: gender, age, preoperative comorbidities, fracture location, preoperative bone density T-score, preoperative ASA classification, operative time, intraoperative blood loss, cement leakage, pulmonary embolism, bone cement toxicity, cement injection volume, puncture site hematoma, infection, cerebrospinal fluid leakage, 1-month postoperative refracture incidence, Visual Analogue Scale (VAS) scores and Oswestry Disability Index (ODI) scores at preoperative, postoperative day 1, and 1-month postoperative timepoints, along with discharge satisfaction.ResultsNo statistically significant differences were observed between the two groups in age, gender, bone mineral density, fracture level distribution, ASA classification, operative time, intraoperative blood loss, cement leakage incidence, or cement injection volume (P > 0.05). In terms of comparing surgical efficacy, there was no statistically significant difference in VAS score and ODI score between the two groups of patients before surgery, 1 day after surgery and 1 month after surgery (P > 0.05). The DSP group showed significantly shorter hospitalization (0.95 ± 0.28 days vs. TIP: 5.20 ± 1.37 days, P < 0.05) and lower hospitalization costs (22,056.66 ± 2,337.61 CNY vs. TIP: 28,341.12 ± 1,711.45 CNY, P < 0.05). Patient satisfaction was significantly higher in the DSP group (96.39 ± 2.26 vs. TIP: 93.87 ± 2.28, P < 0.05), attributable to reduced hospitalization duration and costs. Among 157 day surgery patients, 133 successfully completed the day surgery pathway, while 24 required conversion to traditional inpatient care (DSPT). No significant differences existed in preoperative or 1-month postoperative VAS/ODI scores between DSP and DSPT subgroups (P > 0.05). However, at postoperative day 1, the DSP subgroup demonstrated superior VAS and ODI scores compared to DSPT (P < 0.05).ConclusionsPKP demonstrates safety and efficacy as an day surgery for OVCF, warranting widespread adoption. However, clinicians should note that suboptimal pain relief on postoperative day 1 may represent a primary factor contributing to delayed discharge in some patients.